A Rare Clinical Case of Urachal Adenocarcinoma: Diagnostic Picture Peculiarities According to Radiological Data - V. A. Rebrikova; M. E. Ivannikov; E. V. Egorova; N. V. Nudnov (Вестник рентгенологии и радиологии, 2024)
The article presents the clinical observation of a patient born in 1965, who was examined and treated at the Russian Scientific Center of Roentgenoradiology for tumor of anterior bladder wall detected in May 2023 according to the results of radiation diagnostic methods (ultrasound, computed tomography, magnetic resonance imaging). Analysis of biopsy material obtained during cystoscopy revealed a highly differentiated mucinous urachal adenocarcinoma. Based on the diagnosis of malignant neoplasm of primary urinary tract (urachus) pT3N0M0 stage II, the surgical treatment was proposed. In June 2023, the Bricker procedure was performed: laparoscopic anterior pelvic exenteration with formation of intestinal reservoir. Control examination 3 months after showed no progression of the disease. Asymptomatic development of urachal carcinoma in early stages, peculiarities of its location in pelvic cavity and propensity to metastasis, as well as the rarity of such neoplasm indicate the need for earlier and more accurate verification of the diagnosis. This clinical case demonstrates characteristic clinical and imaging features of urachal adenocarcinoma, which may help radiologists, oncologists, and urologists in making diagnosis and choosing correct treatment tactics.